A polylactic acid matte modified material for 3D printing and preparation method thereof

By using calcium carbonate, talc powder and glass fibers of different particle sizes in polylactic acid 3D printing materials, as well as graft-modified polylactic acid and internal and external lubricants with active functional groups, the precipitation and choke of existing materials during use is solved. The problem of breakage and water absorption achieves a matte effect with high toughness and stable printing performance.

CN118791856BActive Publication Date: 2025-02-18SHANGHAI YINGHUA CHENRUI NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411128172.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-02-18
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

The existing polylactic acid 3D printed matte materials are prone to dissociation during use, causing wire to jam, and continuous printing for a long time can easily block the printer nozzle, which seriously affects the printing quality.

Method used

Calcium carbonate, talc powder and glass fiber of different particle sizes are used as matting agents, combined with graft modified polylactic acid containing active functional groups as a compatible agent, and internal and external lubricants are used to improve material dispersion and printing performance.

Benefits of technology

It realizes the obvious frosted appearance on the surface of the printed product, imparts a matte effect, improves the toughness and printing performance of the modified material, avoids wire breakage and nozzle clogging, and improves production efficiency and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004997072330000011
    Figure BDA0004997072330000011
  • Figure BDA0004997072330000021
    Figure BDA0004997072330000021
  • Figure BDA0004997072330000091
    Figure BDA0004997072330000091
Patent Text Reader

Abstract

The invention discloses a polylactic acid matte modified material for 3D printing and a preparation method thereof, wherein the raw materials are composed of: 55-90 parts of polylactic acid resin, 5-15 parts of toughening agent, 5-30 parts of matting agent, 1-8 parts of compatibilizer, 0-3 parts of plasticizer, 0.3-1 parts of internal lubricant, 0.3-2 parts of external lubricant, 0.1-1 parts of anti-hydrolysis agent, and 0.1-0.6 parts of antioxidant; the matting agent is one or more of calcium carbonate, talcum powder, and glass fiber. The modified material of the present invention has a good application effect in the field of 3D printing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of 3D printing materials, and in particular to a polylactic acid matte modified material for 3D printing and a preparation method thereof. Background Art

[0002] Polylactic acid (PLA) is widely used in the field of 3D printing because of its low printing temperature, easy printing, and printed products are not prone to warping and deformation, and no odor is generated during the printing process, which is beneficial to human health. At present, 3D printed products with matte surface effects are becoming popular in the market, but the surface gloss of products printed with PLA materials is relatively high, which is not suitable for products that require matte effects on the surface; therefore, the development of a PLA 3D printing material with matte effects has become an urgent market demand.

[0003] The existing polylactic acid 3D matte printing materials on the market are very prone to material separation at the extruder die when extruding and drawing 3D printing wires. If the separated material is not cleaned in time, the separated material will follow the wire and cause the wire to break when it is wound, affecting normal production. In addition, the existing polylactic acid matte 3D printing wires are prone to clogging the printer nozzle after long-term continuous printing. The wires absorb water severely when left open in an indoor environment for about a week. If the wires are not dried when printed again, they are prone to wire drawing and poor surface quality of printed parts.

[0004] Therefore, providing a technical means to solve the defects in the use of existing matte polylactic acid 3D printing materials is a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the above problems existing in the prior art, the present invention provides a polylactic acid matte modified material for 3D printing. The modified material of the present invention has a good application effect in the field of 3D printing.

[0006] The technical solution of the present invention is as follows:

[0007] The first object of the present invention is to provide a polylactic acid matte modified material for 3D printing, the types of raw materials and the weight proportions of each raw material are as follows:

[0008]

[0009]

[0010] The matting agent is one or more of calcium carbonate, talcum powder and glass fiber.

[0011] In one embodiment of the present invention, the particle sizes of calcium carbonate and talc are 325-4000 mesh, and the length of glass fiber is 0.2-5 mm.

[0012] Preferably, the matting agent is a mixture of calcium carbonate, talcum powder and glass fiber.

[0013] When calcium carbonate, talcum powder and glass fiber of different particle sizes are used in combination, the surface of the printed product has a very obvious frosted appearance, giving the printed product an excellent matte effect.

[0014] In one embodiment of the present invention, the melt index of the polylactic acid resin is 2-50 g / 10 min, and the test conditions are 190° C. and 2.16 kg.

[0015] Preferably, the polylactic acid is one or more of LX175, LX530, L105, L130 of Total Cobien and REVODE110 of Hisun.

[0016] In one embodiment of the present invention, the toughening agent is one or more of polybutylene terephthalate adipate (PBAT), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polyhydroxyalkanoate (PHA), ethylene vinyl acetate copolymer (EVA), polyolefin resin (POE), ethylene-ethyl acrylate copolymer (EEA), ethylene-methyl acrylate grafted glycidyl methacrylate copolymer, ethylene-n-butyl acrylate grafted glycidyl methacrylate copolymer, and styrene-methyl methacrylate-glycidyl methacrylate copolymer.

[0017] Preferably, the toughening agent is one or more of A400HF of Kingfa, HF701 of Huafeng, 5001MD of Showa Denko, BP350 of Blue Crystal Microbiology, AC2116 of DuPont, KA-40 of TPC, AX8900 of Dow Chemical, DF740 of Mitsui, KL-E4370B of Shanxi Chemical Research Institute, and PTW of Dow Chemical.

[0018] The toughening agent used can significantly improve the toughness of the modified material, so that the prepared printing wire has higher toughness and the wire is not easy to break during long-term printing and clog the printer nozzle; at the same time, the toughening agent with glycidyl methacrylate functional group can also improve the dispersibility of the matting agent in the modified material, so that the printing performance of the wire is stable.

[0019] In one embodiment of the present invention, the compatibilizer is one or more of polylactic acid grafted with epoxy functional groups and polylactic acid grafted with acidic functional groups.

[0020] Preferably, the compatibilizer is one or more of SCONA TPPL 5112PA, SCONA TPPL 1214PA, and SCONATPPL1310PA of BYK Chemical.

[0021] The compatibilizer used can not only improve the compatibility of the toughening agent and the polylactic acid resin, making the modified material tougher; it can also improve the dispersibility of the matting agent in the modified material, so that the printing performance of the printing wire prepared from the modified material is stable, the nozzle discharges smoothly during printing, and it is not easy to break the wire and block the printer nozzle during printing.

[0022] In one embodiment of the present invention, the plasticizer is one or more of acetyl tributyl citrate, tributyl citrate, citric acid fatty acid glyceride, epoxidized soybean oil, and polyethylene glycol.

[0023] In one embodiment of the present invention, the internal lubricant is one or more of ethylene bis stearamide and pentaerythritol stearate.

[0024] In one embodiment of the present invention, the external lubricant is one or more of ST-PA210 from StarBetter, silicone polymers, acrylic multi-block copolymers, PTFE fluoropolymers, and PPA fluoropolymers.

[0025] Preferably, the external lubricant is one or more of PPA-Si of Kunshan Rongdian Company, AC1125 of Dow Chemical, T600 of Shangrui Plastic Company, FR8120 of Shangrui Plastic Company, and EMI-150C of Jiayirong Company.

[0026] Internal lubricants and external lubricants are used in combination. The internal lubrication function of the internal lubricant can reduce the internal friction of the material during material processing, promote the uniform dispersion of the matting agent in the modified material, and make the performance of the printing wire prepared by the modified material uniform; the external lubricant can migrate to the surface of the wire during the production of the printing wire, which can reduce the friction between the polymer melt and the inner wall of the wire extruder die during the production of the wire, thereby reducing the problem of material accumulation at the die; at the same time, the external lubricant migrates to the surface of the polymer melt during the printing process of the wire, reducing the friction between the polymer melt and the inner wall of the printer nozzle during printing, making the material discharge smoother during the printing process and improving the printing performance of the wire.

[0027] In one embodiment of the present invention, the anti-hydrolysis agent is one or more of monomeric carbodiimide and polymeric carbodiimide.

[0028] In one embodiment of the present invention, the anti-hydrolysis agent is one of HyMax1010 and HyMax210 of Langyi Company.

[0029] In one embodiment of the present invention, the antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 1098, and antioxidant 168.

[0030] The second object of the present invention is to provide a method for preparing the above-mentioned polylactic acid matte modified material for 3D printing, comprising the following steps:

[0031] S1. Weigh the raw materials according to the proportion of each component, add them into a high-speed mixer, and mix them at high speed for 5 minutes to 10 minutes to obtain a mixture;

[0032] S2. Add the mixture obtained in S1 into the hopper of a twin-screw extruder, and use the twin-screw extruder to melt, plasticize, mix, extrude, and pelletize the raw materials at a temperature of 150-195° C. to obtain a polylactic acid matte modified material for 3D printing.

[0033] The beneficial technical effects of the present invention are:

[0034] The present invention adopts matting agents with different particle sizes to be used in combination, which can give the printed product an obvious frosted texture appearance, so that the printed product obtains a better matte effect.

[0035] The present invention adopts grafted modified polylactic acid containing active functional groups as a compatibilizer to be used in combination with a toughening agent, which can not only improve the compatibility of the toughening agent with the polylactic acid resin, so that the modified material has better toughness; at the same time, the compatibilizer containing active functional groups can improve the dispersibility of the matting agent in the modified material, so that the printing performance of the printing wire prepared from the modified material is stable.

[0036] This solution uses a combination of internal and external lubricants. The internal lubricant is used to improve the dispersibility of the matting agent in the modified material; the external lubricant reduces the friction with the inner wall of the wire extruder die and the inner wall of the printer nozzle during wire preparation and printing, respectively, thereby solving the problem of material accumulation at the wire extruder die during wire production and the smoothness of wire printing.

[0037] The modified material obtained by the present invention has good application effect in the field of 3D printing. DETAILED DESCRIPTION

[0038] The present invention will be described in detail below in conjunction with the embodiments.

[0039] Example 1

[0040] A polylactic acid matte modified material for 3D printing, the preparation method of which specifically comprises the following steps:

[0041] Step S1, weigh 90 parts of PLA (brand LX175, produced by Total Cobien), 5 parts of PBAT resin (brand A400HF, produced by Kingfa), 4 parts of talc (325 mesh), 1 part of glass fiber (length 5 mm), 1 part of epoxy functional group grafted modified polylactic acid (brand SCONA TPPL 5112PA, produced by BYK Chemical), 3 parts of acetyl tributyl citrate, 0.3 parts of ethylene bis stearamide, 0.3 parts of ST-PA210 (produced by StarBetter), 1 part of anti-hydrolysis agent HyMax1010 (monomer type, produced by Langyi), and 0.1 part of antioxidant 1010, add them into a high-speed mixer, mix at high speed for 5 minutes, and obtain a mixture;

[0042] Step S2, adding the mixture into the hopper of a twin-screw extruder, melting, plasticizing, mixing, extruding, and pelletizing the raw materials at a temperature of 150-195° C. through the twin-screw extruder to obtain a polylactic acid matte modified material for 3D printing, and performing thermodynamic property tests and printing performance tests.

[0043] Printing performance test The 3D printing filament was prepared as follows:

[0044] The obtained polylactic acid matte modified material for 3D printing was added into a 3D printing wire extruder, melted and plasticized at a temperature of 170-210°C to draw a 3D printing wire for printing testing, with a wire diameter of 1.75 mm.

[0045] Example 2

[0046] A polylactic acid matte modified material for 3D printing, the preparation method of which specifically comprises the following steps:

[0047] Step S1, weighing 55 parts of PLA (brand LX530, produced by Total Cobien), 10 parts of PBS resin (brand HF701, produced by Huafeng Company), 5 parts of PBSA resin (brand 5001MD, produced by Showa Denko Company), 20 parts of calcium carbonate (4000 mesh), 5 parts of calcium carbonate (1250 mesh), 5 parts of glass fiber (length 0.2mm), 8 parts of epoxy functional group grafted modified polylactic acid (brand SCONA TPPL 1214PA, produced by BYK Chemical Company), 1 part of pentaerythritol stearate, 2 parts of silicone polymer (brand PPA-Si, produced by Kunshan Rongdian Company), 0.1 part of anti-hydrolysis agent HyMax210 (polymeric type, produced by Langyi Company), 0.3 parts of antioxidant 1010, and 0.3 parts of antioxidant 168, respectively, adding them into a high-speed mixer, mixing at high speed for 5 minutes, and obtaining a mixture;

[0048] Step S2, adding the mixture into the hopper of a twin-screw extruder, melting, plasticizing, mixing, extruding, and pelletizing the raw materials at a temperature of 150-195° C. through the twin-screw extruder to obtain a polylactic acid matte modified material for 3D printing, and performing thermodynamic property tests and printing performance tests.

[0049] Printing performance test The 3D printing filament was prepared as follows:

[0050] The matte modified polylactic acid material for 3D printing was added into the 3D printing wire extruder, melted and plasticized at 170-210°C to draw the 3D printing wire for printing test, with a wire diameter of 1.75 mm.

[0051] Example 3

[0052] A polylactic acid matte modified material for 3D printing, the preparation method of which specifically comprises the following steps:

[0053] Step S1, weighing 70 parts of PLA (brand L105, produced by Total Cobien), 5 parts of PHA resin (brand BP350, produced by Blue Crystal Microbiology), 5 parts of ethylene-ethyl acrylate copolymer (brand AC2116, produced by DuPont), 10 parts of calcium carbonate (2500 mesh), 5 parts of talc (800 mesh), 5 parts of glass fiber (length 0.5 mm), 6 parts of epoxy functional group grafted modified polylactic acid (brand SCONA TPPL 1214PA, produced by BYK Chemical), 2 parts of epoxidized soybean oil, 0.5 parts of pentaerythritol stearate, 1 part of acrylic multi-block copolymer (brand AC1125, produced by DOW), 0.3 parts of anti-hydrolysis agent HyMax210 (polymer type, produced by Langyi), 0.2 parts of antioxidant 1076, and 0.2 parts of antioxidant 168, respectively, adding them into a high-speed mixer, mixing at high speed for 5 minutes, and obtaining a mixture;

[0054] Step S2, adding the mixture into the hopper of a twin-screw extruder, melting, plasticizing, mixing, extruding, and pelletizing the raw materials at a temperature of 150-195° C. through the twin-screw extruder to obtain a polylactic acid matte modified material for 3D printing, and performing thermodynamic property tests and printing performance tests.

[0055] Printing performance test The 3D printing filament was prepared as follows:

[0056] The obtained polylactic acid matte modified material for 3D printing was added into a 3D printing wire extruder, melted and plasticized at a temperature of 170-210°C to draw a 3D printing wire for printing testing, with a wire diameter of 1.75 mm.

[0057] Example 4

[0058] A polylactic acid matte modified material for 3D printing, the preparation method of which specifically comprises the following steps:

[0059] Step S1, respectively weighing 80 parts of PLA (brand name REVODE110, produced by Hisun Company), 3 parts of EVA resin (brand name KA-40, produced by TPC Company), 5 parts of ethylene-methyl acrylate grafted glycidyl methacrylate copolymer (brand name AX8900, produced by DOW Company), 10 parts of talc (3000 mesh), 2 parts of glass fiber (length 3mm), 4 parts of epoxy functional group grafted modified polylactic acid (brand name SCONA TPPL 5112PA, produced by BYK Chemical Company), 1 part of polyethylene glycol 8000, 0.4 parts of ethylene bis stearamide, 0.8 parts of PTFE-based fluorine-containing polymer (brand name T600, produced by Shangrui Plastic Company), 0.5 parts of anti-hydrolysis agent HyMax210 (polymer type, produced by Langyi Company), 0.2 parts of antioxidant 1098, and 0.2 parts of antioxidant 168, adding them into a high-speed mixer, mixing at high speed for 5 minutes, to obtain a mixture;

[0060] Step S2, adding the mixture into the hopper of a twin-screw extruder, melting, plasticizing, mixing, extruding, and pelletizing the raw materials at a temperature of 150-195° C. through the twin-screw extruder to obtain a polylactic acid matte modified material for 3D printing, and performing thermodynamic property tests and printing performance tests.

[0061] Printing performance test The 3D printing filament was prepared as follows:

[0062] The obtained polylactic acid matte modified material for 3D printing was added into a 3D printing wire extruder, melted and plasticized at a temperature of 170-210°C to draw a 3D printing wire for printing testing, with a wire diameter of 1.75 mm.

[0063] Example 5

[0064] A polylactic acid matte modified material for 3D printing, the preparation method of which specifically comprises the following steps:

[0065] Step S1, weigh 80 parts of PLA (brand L130, produced by Total Cobien), 3 parts of POE resin (brand DF740, produced by Mitsui Company), 3 parts of styrene-methyl methacrylate-glycidyl methacrylate copolymer (brand KL-E4370B, produced by Shanxi Chemical Research Institute), 12 parts of calcium carbonate (1250 mesh), 2 parts of talc (1250 mesh), 5 parts of acidic functional group grafted modified polylactic acid (brand SCONA TPPL 1310PA, produced by BYK Chemical Company), 1 part of tributyl citrate, 0.4 parts of ethylene bisstearamide, 1.5 parts of silicone polymer (brand EMI-150C, produced by Jiayirong Company), 0.8 parts of anti-hydrolysis agent HyMax1010 (polymeric type, produced by Langyi Company), 0.4 parts of antioxidant 1076, and 0.2 parts of antioxidant 168, add them into a high-speed mixer, mix at high speed for 5 minutes, and obtain a mixture;

[0066] Step S2, adding the mixture into the hopper of a twin-screw extruder, melting, plasticizing, mixing, extruding, and pelletizing the raw materials at a temperature of 150-195° C. through the twin-screw extruder to obtain a polylactic acid matte modified material for 3D printing, and performing thermodynamic property tests and printing performance tests.

[0067] Printing performance test The 3D printing filament was prepared in the following manner: the obtained polylactic acid matte modified material for 3D printing was added into a 3D printing filament extruder, and melted and plasticized at a temperature of 170-210°C to draw a 3D printing filament for printing test, with a filament diameter of 1.75 mm.

[0068] Example 6

[0069] A polylactic acid matte modified material for 3D printing, the preparation method of which specifically comprises the following steps:

[0070] Step S1, weighing 68 parts of PLA (brand L130, produced by Total Cobien), 7 parts of ethylene-butyl acrylate grafted glycidyl methacrylate copolymer (brand PTW, produced by DOW), 20 parts of calcium carbonate (1250 mesh), 5 parts of glass fiber (length 0.5 mm), 8 parts of epoxy functional group grafted modified polylactic acid (brand SCONA TPPL 5112PA, produced by BYK Chemical), 2 parts of citric acid fatty acid glyceride, 0.6 parts of ethylene bis stearamide, 1.2 parts of PPA-type fluorinated polymer (brand FR8120, produced by Shangrui Plastics), 0.8 parts of anti-hydrolysis agent HyMax1010 (polymer type, produced by Langyi), and 0.6 parts of antioxidant 1076, respectively, adding them into a high-speed mixer, mixing at high speed for 5 minutes, and obtaining a mixture;

[0071] Step S2, adding the mixture into the hopper of a twin-screw extruder, melting, plasticizing, mixing, extruding, and pelletizing the raw materials at a temperature of 150-195° C. through the twin-screw extruder to obtain a polylactic acid matte modified material for 3D printing, and performing thermodynamic property tests and printing performance tests.

[0072] Printing performance test The 3D printing filament was prepared as follows:

[0073] The obtained polylactic acid matte modified material for 3D printing was added into a 3D printing wire extruder, melted and plasticized at a temperature of 170-210°C to draw a 3D printing wire for printing testing, with a wire diameter of 1.75 mm.

[0074] Comparative Example 1

[0075] A polylactic acid 3D printing matte modified material, the preparation method of which specifically comprises the following steps:

[0076] Step S1, weighing 68 parts of PLA (brand L130, produced by Total Cobien), 7 parts of ethylene-butyl acrylate grafted glycidyl methacrylate copolymer (brand PTW, produced by DOW), 25 parts of calcium carbonate (1250 mesh), 8 parts of epoxy functional group grafted modified polylactic acid (brand SCONA TPPL 5112PA, produced by BYK Chemical), 2 parts of citric acid fatty acid glyceride, 0.6 parts of ethylene bisstearamide, 1.2 parts of PPA-type fluorinated polymer (brand FR8120, produced by Shangrui Plastics), 0.8 parts of anti-hydrolysis agent HyMax1010 (polymer type, produced by Langyi), and 0.6 parts of antioxidant 1076, respectively, adding them into a high-speed mixer, mixing at high speed for 5 minutes, and obtaining a mixture;

[0077] Step S2, adding the mixture into the hopper of a twin-screw extruder, melting, plasticizing, mixing, extruding, and pelletizing the raw materials at a temperature of 150-195° C. through the twin-screw extruder to obtain a polylactic acid 3D printing matte modified material, and performing a thermodynamic property test and a printing performance test.

[0078] Printing performance test The 3D printing filament was prepared as follows:

[0079] The obtained polylactic acid 3D printing matte modified material was added into the 3D printing wire extruder, melted and plasticized at a temperature of 170-210°C to draw the 3D printing wire for printing test, with a wire diameter of 1.75 mm.

[0080] Comparative Example 2

[0081] A polylactic acid 3D printing matte modified material, the preparation method of which specifically comprises the following steps:

[0082] Step S1, weighing 68 parts of PLA (brand L130, produced by Total Cobien), 7 parts of ethylene-butyl acrylate grafted glycidyl methacrylate copolymer (brand PTW, produced by DOW), 20 parts of calcium carbonate (1250 mesh), 5 parts of glass fiber (length 0.5 mm), 2 parts of citric acid fatty acid glyceride, 0.6 parts of ethylene bisstearamide, 1.2 parts of PPA-type fluorinated polymer (brand FR8170, produced by Shangrui Plastics), 0.8 parts of anti-hydrolysis agent HyMax1010 (polymeric type, produced by Langyi), and 0.6 parts of antioxidant 1076, respectively, adding them into a high-speed mixer, mixing at high speed for 5 minutes, and obtaining a mixture;

[0083] Step S2, adding the mixture into the hopper of a twin-screw extruder, melting, plasticizing, mixing, extruding, and pelletizing the raw materials at a temperature of 150-195° C. through the twin-screw extruder to obtain a polylactic acid 3D printing matte modified material, and performing a thermodynamic property test and a printing performance test.

[0084] Printing performance test The 3D printing filament was prepared as follows:

[0085] The obtained polylactic acid 3D printing matte modified material was added into the 3D printing wire extruder, melted and plasticized at a temperature of 170-210°C to draw the 3D printing wire for printing test, with a wire diameter of 1.75 mm.

[0086] Comparative Example 3

[0087] A polylactic acid 3D printing matte modified material, the preparation method of which specifically comprises the following steps:

[0088] Step S1, weighing 68 parts of PLA (brand L130, produced by Total Cobien), 7 parts of ethylene-butyl acrylate grafted glycidyl methacrylate copolymer (brand PTW, produced by DOW), 20 parts of calcium carbonate (1250 mesh), 5 parts of glass fiber (length 0.5 mm), 2 parts of citric acid fatty acid glyceride, 0.6 parts of ethylene bisstearamide, 0.8 parts of anti-hydrolysis agent HyMax1010 (polymer type, produced by Langyi Company), and 0.6 parts of antioxidant 1076, respectively, adding them into a high-speed mixer, mixing at high speed for 5 minutes, and obtaining a mixture;

[0089] Step S2, adding the mixture into the hopper of a twin-screw extruder, melting, plasticizing, mixing, extruding, and pelletizing the raw materials at a temperature of 150-195° C. through the twin-screw extruder to obtain a polylactic acid 3D printing matte modified material, and performing a thermodynamic property test and a printing performance test.

[0090] Printing performance test The 3D printing filament was prepared as follows:

[0091] The obtained polylactic acid 3D printing matte modified material was added into the 3D printing wire extruder, melted and plasticized at a temperature of 170-210°C to draw the 3D printing wire for printing test, with a wire diameter of 1.75 mm.

[0092] Test example:

[0093] Izod notched impact strength test: standard is GB / T 1843-2008.

[0094] Gloss test: standard is ASTM D2457-21, measuring angle is 60°.

[0095] Printing performance: Place the filament on the printer and print the product according to the model. Visually inspect the nozzle discharge smoothness during printing, the frosted texture of the printed product, and whether there is any breakage or nozzle blockage during continuous printing for 48 hours.

[0096] Die buildup performance: Add the modified material into the wire extruder for continuous production for more than 1 hour, and observe the material buildup at the die of the extruder during wire production.

[0097] The test results of the modified materials and wire printing performance in Examples 1-6 and Comparative Examples 1-3 are shown in Table 1:

[0098] Table 1

[0099]

[0100] As can be seen from Table 1, the modified material not only has high toughness, but also uses different particle sizes of calcium carbonate, talcum powder and glass fiber to significantly improve the frosted texture of the printed product. The use of compatibilizers and internal and external lubricants can greatly improve the dispersibility of the matting agent, making the 3D printing wire prepared by the modified material print smoothly, not easy to break the wire and block the printer nozzle, and can effectively reduce the accumulation of material at the die of the extruder during wire production, ensuring production efficiency and product qualification rate.

[0101] The specific embodiments of the present invention are described in detail above, but they are only examples, and the present invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions made to the present invention are also within the scope of the present invention. Therefore, the equalization changes and modifications made without departing from the spirit and scope of the present invention should be included in the scope of the present invention.

Claims

1. A polylactic acid matte modified material for 3D printing, characterized in that: The types of raw materials and the weight proportions of each raw material are: The matting agent is a mixture of calcium carbonate, talcum powder and glass fiber; the particle size of calcium carbonate and talcum powder is 325-4000 mesh, and the length of glass fiber is 0.2-5mm; The internal lubricant is one or more of ethylene bis stearamide and pentaerythritol stearate; the external lubricant is one or more of ST-PA210 of StarBetter, silicone polymer, acrylic multi-block copolymer, PTFE fluoropolymer and PPA fluoropolymer.

2. The polylactic acid matte modified material for 3D printing according to claim 1, characterized in that: The melt index of the polylactic acid resin is 2-50 g / 10 min, and the test conditions are 190° C. and 2.16 kg.

3. The polylactic acid matte modified material for 3D printing according to claim 1, characterized in that: The toughening agent is one or more of polybutylene terephthalate adipate, polybutylene succinate, polybutylene succinate adipate, polyhydroxyalkanoate, ethylene vinyl acetate copolymer, polyolefin resin, ethylene-ethyl acrylate copolymer, ethylene-methyl acrylate grafted glycidyl methacrylate copolymer, ethylene-n-butyl acrylate grafted glycidyl methacrylate copolymer, and styrene-methyl methacrylate-glycidyl methacrylate copolymer.

4. The polylactic acid matte modified material for 3D printing according to claim 1, characterized in that: The compatibilizer is one or more of polylactic acid grafted with epoxy functional groups and polylactic acid grafted with acidic functional groups.

5. The polylactic acid matte modified material for 3D printing according to claim 1, characterized in that: The plasticizer is one or more of acetyl tributyl citrate, tributyl citrate, citric acid fatty acid glyceride, epoxidized soybean oil, and polyethylene glycol.

6. The polylactic acid matte modified material for 3D printing according to claim 1, characterized in that: The anti-hydrolysis agent is one or more of monomeric carbodiimide and polymeric carbodiimide; the antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 1098 and antioxidant 168.

7. A method for preparing the polylactic acid matte modified material for 3D printing according to claim 1, characterized in that: The preparation method comprises the following steps: S1. Weigh the raw materials according to the proportion of each component, add them into a high-speed mixer, and mix them at high speed for 5-10 minutes to obtain a mixture; S2. Add the mixture obtained in S1 into the hopper of a twin-screw extruder, and use the twin-screw extruder to melt, plasticize, mix, extrude, and pelletize the raw materials at a temperature of 150-195° C. to obtain a polylactic acid matte modified material for 3D printing.

Citation Information

Patent Citations

  • PLA modified material applied to 3D printing of large casting molds, and method of PLA modified material

    CN106009572A

  • High-toughness matte modified polylactic acid material for 3D printing and preparation method of high-toughness matte modified polylactic acid material

    CN109575539A

  • Modified polylactic acid and wood powder composite for 3D printing and preparing method

    CN110105735A